Prospective Assessment of Pain and Comfort in Chronic Pain Patients Undergoing Interventional Pain Management Procedures. Issue 2 (18th April 2017) - Simopoulos, Thomas; Leffler, Daniel; Barnett, Sheila; Campbell, Devon; Lian, Shu Jing; Gill, Jatinder S
Abstract: Objective: Interventional pain management procedures have an important role in the management of chronic pain. The present study seeks to identify the proportion of patients who experience severe pain during pain procedures either with or without sedation. There is then an attempt to identify any association of high pain levels with factors such as age, gender, ethnicity, preprocedure pain level, procedure type, tobacco use, and baseline pharmaceuticals taken for both pain and/or mood disorder management. Methods: This is a prospective survey study evaluating patients' discomfort during interventional pain procedures in an outpatient academic facility. Patient discomfort was assessed by the PROcedural Sedation Assessment Survey (PROSAS) and modified for nonsedation cases. Results: There were 155 patients in the survey, with 20 of these receiving nonspinal injections. Of the remaining 135 patients who underwent spinal injections, only 10 received conscious sedation. On average, 14.2% experienced severe pain during spinal injections, whereas 20% experienced severe pain with nonspinal injections. Though few patients received conscious sedation, most of these (60%) experienced high levels of pain. There was no correlation between level of procedural pain with age, gender, ethnicity, preprocedure pain level, procedure type, tobacco use, or medication type used. Conclusions: The majority of patients who undergo nonsedated interventional pain management procedures do not experience severe pain. There is a small but appreciable group of subjects who seem to experience severe pain that cannot be correlated to any particular clinical characteristic in a standard patient evaluation. Even with standard conscious sedation, there is no clear best method to ensure patient comfort for this high–pain level group.